Die Wunden des Staates : Kriegsopfer und Sozialstaat in Österreich 1914-1938 - Pawlowsky, Verena; Wendelin, Harald (2015)
The study’s subject is the assistance for the victims of World War I in Austria. It explains the numerous measures taken in favour of disabled veterans and war widows during the war and in the post-war period and describes the powerful organisations of the invalids. The assistance for war victims expressed very early social policy as supported by the state.